(untitled) (Journal of Global Arts Studies, 2024)
Background: At present, with the development of society, a single language system can no longer satisfy the diversified ideographic system, and the research on multimodal grammar has formed a hot spot in many fields, but there are only a few studies in the direction of Chinese painting. Objective: On the basis of previous research results, the article tries to construct a research framework of multimodal visual grammar applicable to Chinese figure paintings, taking Gu Kaizhi’s "Female Historian’s Picture" as an example to explore the rationality and scientificity of the article’s framework. Methods: Using literature research method, case study analysis method, integrating previous research results, and starting from a specific case to try to establish a research method of Chinese figure painting under the multimodal perspective. Results: It can be found through the research of the above steps that by analyzing the multimodal visual grammar of Chinese paintings, more profound conclusions can be drawn from the research of the picture. Conclusion: Taking the Female Historian as an example, which is suitable for multimodal grammatical analysis, we can try to establish a framework for multimodal analysis of Chinese paintings afterward, so that we can start from a specific case and establish a perfect grammatical structure for multimodal analysis of Chinese paintings in the basic research.